PENERAPAN METODE SQ3R (SURVEY, QUESTION, READ, RECITE,REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS IV SDN 116 ENREKANG - Fatima Azzahra; Muh. Idham Haliq; Rahmat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve the Indonesian language learning outcomes of fourth-grade students at SDN 116 Enrekang through the implementation of the SQ3R (Survey, Question, Read, Recite, Review) method. The study employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 16 fourth-grade students. The results showed that the implementation of the SQ3R method improved students’ learning outcomes. The average score increased from 69.75 in the pre-action stage to 75.75 in Cycle I and 83.25 in Cycle II. Learning mastery also improved from 50% in the pre-action stage to 68.75% in Cycle I and 93.75% in Cycle II. The findings indicate that the SQ3R method effectively improves Indonesian language learning outcomes among fourth-grade students at SDN 116 Enrekang. Keywords: SQ3R Method (Survey, Question, Read, Recite, Review), Learning Outcomes, Indonesian Language.